2023
DOI: 10.48550/arxiv.2302.02028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyzing the Large-Scale Bulk Flow using CosmicFlows4: Increasing Tension with the Standard Cosmological Model

Abstract: We present an estimate of the bulk flow in a volume of radii 150−200h −1 Mpc using the minimum variance (MV) method with data from the CosmicFlows-4 (CF4) catalog. The addition of new data in the CF4 has resulted in an increase in the estimate of the bulk flow in a sphere of radius 150h −1 Mpc relative to the CosmicFlows-3 (CF3). This bulk flow has less than a 0.03% chance of occurring in the Standard Cosmological Model (ΛCDM) with cosmic microwave background derived parameters. Given that the CF4 is deeper th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Despite of the simplicity and overall observational consistency of the CP, a few challenges have developed during the past several years which appear to consistently question the validity of the CP on cosmological scales larger than 100M pc and motivate further tests to be imposed on its validity. Some of these challenges pointing to preferred directions on large cosmological scales include the quasar dipole [2][3][4][5][6], the radio galaxy dipole [7][8][9], the bulk velocity flow [10][11][12][13], the dark velocity flow [14], the CMB anomalies [15,16], the galaxy spin alignment [17][18][19], the galaxy cluster anisotropies [20], and a possible SnIa dipole [21,22]. These observational challenges of the CP may be indirectly connected with other tensions of the standard ΛCDM model including the Hubble [23][24][25] and growth ten- * leandros@uoi.gr sions [26][27][28][29] where the best fit parameter values of the model H 0 and σ 8 appear to be inconsistent when probed by different observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the simplicity and overall observational consistency of the CP, a few challenges have developed during the past several years which appear to consistently question the validity of the CP on cosmological scales larger than 100M pc and motivate further tests to be imposed on its validity. Some of these challenges pointing to preferred directions on large cosmological scales include the quasar dipole [2][3][4][5][6], the radio galaxy dipole [7][8][9], the bulk velocity flow [10][11][12][13], the dark velocity flow [14], the CMB anomalies [15,16], the galaxy spin alignment [17][18][19], the galaxy cluster anisotropies [20], and a possible SnIa dipole [21,22]. These observational challenges of the CP may be indirectly connected with other tensions of the standard ΛCDM model including the Hubble [23][24][25] and growth ten- * leandros@uoi.gr sions [26][27][28][29] where the best fit parameter values of the model H 0 and σ 8 appear to be inconsistent when probed by different observational data.…”
Section: Introductionmentioning
confidence: 99%
“…[39] complied the sample of Luminous Red Galaxies (LRG) from the Sloan Digital Sky Survey to test the homogeneity and found that the Cosmological Principle does not hold up to the length scale of 300 h −1 Mpc. Furthermore, large scale bulk flow observations are in significant tension with the ΛCDM [40,41]. There also exist several anomalies in the CMB data, JCAP06(2024)019 such as, the hemispherical power asymmetry [42], alignment of quadrupole and octopole harmonics [43,44] and dipole modulation in the CMB polarization [45].…”
Section: Introductionmentioning
confidence: 99%